Early Onset Dementia and Non Pharmalogical Treatment: A Case Report - Kusuma, Susana anggar; Bessing, Yulia Fatima; Yulianti, Erikavitri (Jurnal Psikiatri Surabaya, 2025)
Introduction: Early-onset dementia (EOD), defined as dementia occurring before the age of 65, leads to progressive cognitive and functional decline that disrupts patients’ productivity, family roles, and social well-being. With limited pharmacological efficacy, non-pharmacological approaches are increasingly recognized as essential to improve patients’ quality of life. Methods: This report describes a 59-year-old female presenting with severe cognitive impairment and daily functional decline. Clinical evaluation involved psychiatric interviews, physical examinations, and standardized cognitive assessments, including the Mini-Mental State Examination (MMSE), Clinical Dementia Rating (CDR), and Barthel Index. Written consent was obtained from the family. Results: The patient displayed severe memory loss, disorientation, and inability to perform basic activities. Cognitive testing confirmed MMSE: 0, CDR: 18, and Barthel Index: 40, indicating severe dementia with high dependence. No prior psychiatric or neurological illness was reported. Non-pharmacological interventions, such as cognitive rehabilitation, stimulation, and training, were identified as effective in maintaining residual abilities, delaying progression, and improving well-being. Conclusion: EOD requires early recognition and comprehensive management due to its profound personal and social impact. Although curative options are unavailable, non-pharmacological therapies offer meaningful benefits by enhancing cognitive function, supporting independence, and improving quality of life for patients and families.